Literature Study : Complementary Therapy in Overcoming Dysmenorrhea - Tri Sartika; Lina Contesa; Deby Meitia Sandi (Lembaga Pengembangan Kinerja Dosen, 2025)
Around 50-90% of women in the world experience dysmenorrhea. The prevalence of dysmenorrhea in Indonesia is reported to reach 64.25%, where 54.89%. Complementary therapy is an alternative to overcome dysmenorrhea because it is considered more natural and has minimal side effects. This study aims to review research articles related to complementary therapies that can be used to overcome dysmenorrhea. literature search through academic databases such as Google Scholar, PubMed and ScienceDirect. Literature selection is carried out based on inclusion criteria (scientific articles in the last 5 years, English/Indonesian, relevant topics) and exclusion (irrelevant articles, no abstract/full-text). Interventions such as physical therapy (yoga and stretching), compress therapy, aromatherapy, acupressure, reflexology, and consumption of natural ingredients provide safe and natural solutions to reduce pain intensity. The selection of the appropriate method can be adjusted according to individual preferences, accessibility, and the severity of the pain experienced.